Trends of depression and anxiety during massive civil unrest and COVID-19 in Hong Kong, 2019–2020. (January 2022) - Hou, Wai Kai; Li, Tsz Wai; Liang, Li; Liu, Huinan; Ettman, Catherine K.; Hobfoll, Stevan E.; Lee, Tatia Mei-Chun; Galea, Sandro
Abstract: Both COVID-19 and unrest are posing a significant threat to population mental health across the globe. This study examined trends of probable depression and anxiety during a time of civil unrest and concurrent COVID-19 in Hong Kong. Four random digit dialing telephone surveys were conducted in July 2019 ( n  = 1112), February–March 2020 ( n  = 2003), April–May 2020 ( n  = 2008), and July–August 2020 ( n  = 2034). The prevalence of probable depression increased from 25.7% (95% CI: 23.2–28.3) in July 2019 to 28.2% (95% CI: 26.2–30.1) in February–March 2020, and then decreased to 15.3% (95% CI: 14.0–17.0) in April–May 2020 and 13.7% (95% CI: 12.2–15.2) in July–August 2020. The prevalence of probable anxiety was 19.2% (95% CI: 17.5–20.9) in February–March 2020 and then stabilized in April–May 2020 and July–August 2020 (14.1%, 95% CI: 12.0–15.8). Probable depression and anxiety were more prevalent among persons with high relative to low daily routine disruptions. Combined high unrest-COVID-19 stress was associated with probable depression and anxiety across all persons; high unrest stress alone was associated with probable mental disorders at high daily routine disruptions. Civil unrest and COVID-19 are jointly associated with depression and anxiety among Hong Kong citizens. While population mental health improved, daily routine disruptions is a risk factor of mental disorders at every time-point. Highlights: Combined Unrest-COVID-19 stress has profound impact on mental health. Mental health risk is more prevalent among persons who experienced both stressors. Persons with disrupted daily routines are prone to adverse psychological outcomes. Return to regular daily routines is a protective factor against mental health risks.